Family History of Hypertension Predicts Thyroid Cancer Risk in Women: A Population‐Based Cross‐Sectional Study With Integrative Machine Learning and Genomic Analyses - Zijin Wang; Yanhui Lin; Fanke Meng; Yuxin Sun; Ziran Zhang; Tong Wu; Min Fu; Fanye Wu; Zhengran Li; Zejun Chen (Cancer Medicine)
ABSTRACT Introduction Thyroid cancer is one of the most common endocrine malignancies globally, with a markedly higher incidence in women. Although pregnancy‐induced hypertension is recognized as a risk factor, the underlying mechanisms linking hypertension and thyroid cancer remain poorly understood. This study explores the gender‐specific associations between family history of hypertension and thyroid cancer, integrating clinical characteristics with genetic insights. Methods In this large‐scale cross‐sectional study conducted in China, clinical and lifestyle data were collected from 52,963 participants, including 296 thyroid cancer cases. An interpretable ensemble machine learning model was constructed to evaluate risk factors, and odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. Additionally, the Cox proportional hazards model was applied to identify significant hypertension‐related genes, and Kaplan–Meier analyses were used to compare overall survival, clinical stages, and immune cell infiltration between high‐ and low‐risk groups. Results Our analysis revealed that individuals with a family history of hypertension exhibited a significantly altered rate of thyroid cancer (p < 0.001). In particular, among women, a positive family history increased thyroid cancer risk (OR = 1.53, 95% CI: 1.09–2.14, p = 0.04) and emerged as a key predictor in the machine learning model. Genetic analyses identified overlapping genes—most notably FOXD3, F10, and SLC12A5—whose aberrant expression was associated with poorer five‐year survival and distinct immune cell profiles. Conclusions Our study provides novel clinical and genetic evidence that family history of hypertension is significantly associated with thyroid cancer in women. Integrating hypertension‐related screening with genetic profiling may enhance risk stratification and aid in the development of personalized management strategies to reduce overtreatment.